2016
DOI: 10.3130/jaabe.15.73
|View full text |Cite
|
Sign up to set email alerts
|

Factors of a Surveillance Environment that Affect Burglaries in Commercial Districts

Abstract: This study proposes a surveillance approach that will enhance safety in commercial districts. The authors identified physical factors that increase the likelihood of burglaries, and analyzed a commercial zone in relation to these factors to create a crime-free urban area. The study was conducted in Yeoksam-dong, a neighborhood of Gangnam-gu (the Gangnam District) in Seoul, Korea's capital. Yeoksam-dong has a large floating population. The authors found that: (1) In commercial districts, burglaries on footpaths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…Besides, the findings also help the designer to identify the place that can reduce visibility by controlling the street space. As conclusion, layout with good permeable design gives a tendency to smallest number of burglary, and this support the evidence suggest by several studies that linking the permeability and layout design (Kigawa and Seo, 2017;Summers and Johnson, 2017;Bolton et al, 2017;Byun, 2016;Varoudis and Penn, 2015;Ward et al, 2014;Othman, 2014;and Nes and Rueb, 2013). By emphasizing the space used in the future, it is fulfilling the strategy of the safe city program as environmental design initiatives and preventing crime through environmental design.…”
Section: Conclusion and Recommendationssupporting
confidence: 86%
See 1 more Smart Citation
“…Besides, the findings also help the designer to identify the place that can reduce visibility by controlling the street space. As conclusion, layout with good permeable design gives a tendency to smallest number of burglary, and this support the evidence suggest by several studies that linking the permeability and layout design (Kigawa and Seo, 2017;Summers and Johnson, 2017;Bolton et al, 2017;Byun, 2016;Varoudis and Penn, 2015;Ward et al, 2014;Othman, 2014;and Nes and Rueb, 2013). By emphasizing the space used in the future, it is fulfilling the strategy of the safe city program as environmental design initiatives and preventing crime through environmental design.…”
Section: Conclusion and Recommendationssupporting
confidence: 86%
“…In a term of surveillance and layout, identifying the possible crime is recommended studying on the street configuration at the micro-level. In general, at least with layout design, the evidence suggests that more porous layout can reduce the crime rate (Kigawa and Seo, 2017;Summers and Johnson, 2017;Bolton et al, 2017;Byun, 2016;Varoudis and Penn, 2015;Ward et al, 2014;Othman, 2014;and Nes and Rueb, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also in the United States, Loomis, Marshall, Wolf, Runyan, and Butts (2002) found that bright exterior light was associated with reduction of homicides in workplaces. Byun and Ha (2016) found that lighting was associated with the reduction of burglaries in Seoul, South Korea. Peek-Asa and Casteel (2010) indicated that good lighting presents a reduction of total robbery, controlling for a number of factors in the retail setting.…”
Section: The Effect Of Lighting On Crime and Fearmentioning
confidence: 98%
“…The setup for the Grasshopper model builder is based on the suitability of human vision such as the earlier theory of environmental planning (Spreiregen 1965). Byun and Ha (2016) noted that the vision of the human eye is limited to a distance of 4000 feet, while the maximum length for seeing body gestures is up to 450 feet. Therefore, the isovist radius was set to both ranges to obtain multiple visual readings.…”
Section: Spatial Analysis and Layout Modelingmentioning
confidence: 99%